PEMANFAATAN ALAT PERAGA SEBAGAI SUMBER BELAJAR DALAM PELAKSANAAN PEMBELAJARAN MATEMATIKA - Nurhasanah Nurhasanah (Fitrah, 2021)
This study aims to determine the use of teaching aids as a source of learning mathematics in supporting and increasing students' knowledge. This study uses a descriptive qualitative approach. The subject of this study was a teacher in the field of mathematics at the State Junior High School 2 Bima City. This research is focused on the use of teaching aids by teachers as a source of learning mathematics. To obtain valid data accuracy in the study, the researcher used the following instruments: Interview (Interview) via mobile phone with a class teacher who teaches mathematics subjects which aims to obtain data directly from the research site. The results of the study indicate that the use of teaching aids in schools has not been used optimally, so to further maximize the use of teaching aids, it is expected that the principal's role in monitoring teachers and students to use teaching aids is expected.